KARAKTERISASI ISOLAT BAKTERI PENGHASIL SELULOSA DARI BUAH NAGA MERAH (Hylocereus polyrhizus) - Siska Nuryanti; Fitriana Fitriana; A. Rini Pratiwi (As-Syifaa Jurnal Farmasi, 2021)
Cellulose is a natural polymer widely used for general industrial purposes. The development of science utilizes bacteria from certain fruits to produce biosellulose. Red dragon fruit (Hylocereus polyrhizus) contains a lot of sugar which can be bioconverted to cellulose by cellulose- producing lines. The research aimed to obtain bacteria from red dragon fruit with the potential to produce cellulose, then conduct morphological and biochemical characterization. The research was conducted by the isolation of bacteria from the fruit, purification, and screening tests using Hestrin-Schramm medium. The isolates obtained were characterized morphologically through macroscopic and microscopic observation and the biochemically through catalase test, carbohydrate fermentation, starch and gelatin hydrolysis, motility, and IMViC (Indole, Methyl red, Voges- Proskauer, Citrate). The results showed that 4 bacterial isolates had the potential to produce cellulose. Based on Bergey's Manual of Systematic Bacteriology, 3 bacterial genera were obtained, namely Acetobacter, Gluconacetobacter, and Azotobacter. The results of the characteristics of the isolates obtained at IBBN 2-2 were positive in the catalase test, sucrose and lactose fermentation, and methyl red. IBBN 3-1 was positive in the catalase test, sugar fermentation, starch hydrolysis, methyl red, and citrate. IBBN 3-2 was positive in the sucrose and glucose fermentation test, gelatin hydrolysis and 4-1 IBBN was positive in the sucrose fermentation test and gelatin hydrolysis.